Cannabinoid Receptor-2 Ameliorates Inflammation in Murine Model of Crohn's Disease. (17th July 2017) - Leinwand, Kristina L; Jones, Ashleigh A; Huang, Rick H; Jedlicka, Paul; Kao, Daniel J; de Zoeten, Edwin F; Ghosh, Soumita; Moaddel, Ruin; Wehkamp, Jan; Ostaff, Maureen J; Bader, Jutta; Aherne, Carol M; et al.
Abstract: Background and Aims: Cannabinoid receptor stimulation may have positive symptomatic effects on inflammatory bowel disease [IBD] patients through analgesic and anti-inflammatory effects. The cannabinoid 2 receptor [CB2 R] is expressed primarily on immune cells, including CD4 + T cells, and is induced by active inflammation in both humans and mice. We therefore investigated the effect of targeting CB2 R in a preclinical IBD model. Methods: Employing a chronic ileitis model [TNF ΔARE/+ mice], we assessed expression of the CB2 R receptor in ileal tissue and on CD4 + T cells and evaluated the effect of stimulation with CB2 R-selective ligand GP-1a both in vitro and in vivo . Additionally, we compared cannabinoid receptor expression in the ilea and colons of healthy human controls with that of Crohn's disease patients. Results: Ileal expression of CB2 R and the endocannabinoid anandamide [AEA] was increased in actively inflamed TNF ∆ARE/+ mice compared with controls. CB2 R mRNA was preferentially induced on regulatory T cells [Tregs] compared with T effector cells, approximately 2.4-fold in wild-type [WT] and 11-fold in TNF ∆ARE/+ mice. Furthermore, GP-1a enhanced Treg suppressive function with a concomitant increase in IL-10 secretion. GP-1a attenuated murine ileitis, as demonstrated by improved histological scoring and decreased inflammatory cytokine expression. Lastly, CB2 R is downregulated in both chronically inflamed TNF ∆ARE/+ mice and in IBD patients. Conclusions: In summary, the endocannabinoid system is induced in murine ileitis but is downregulated in chronic murine and human intestinal inflammation, and CB2 R activation attenuates murine ileitis, establishing an anti-inflammatory role of the endocannabinoid system.